LESSONS FROM VIETNAM’S SOLAR POWER PLANT GROWTH DEVELOPMENT FOR INDONESIA TO REACH NET ZERO EMISSION: Pembelajaran Pertumbuhan PLTS Vietnam bagi Tantangan Indonesia Menuju Net Zero Emission - Irwan Wakhidiyanto (Pusat Pengembangan Sumber Daya Manusia Minyak dan Gas Bumi, 2022)
CO2 gas emissions are increasingly massive, one of which is caused by the generation of energy from fossils in many countries that poses a threat to climate change. The global world has agreed on the Paris Agreement in 2016 to reduce carbon emissions in 2050. ASEAN countries are also taking concrete steps, especially in the electricity sector by seeking renewable energy sources. At present Vietnam has succeeded in becoming the leading country in ASEAN in the solar power development sector in order to meet its electricity needs and also in order to reduce carbon emissions. Indonesia is one of the countries that has ratified the agreement has made a